MEDICATION ADHERENCE: UNDERSTANDING THE CHALLENGES AMONG THE ELDERLY - Usman Jaffer; Che Mohd Nasril Che Mohd Nassir; Mohamed Ayaaz Ahmed; Rahmah Ahmad H. Osman; Abdul Muhaimin Adam; Faqyhah Mohd Khair; Muhammad Mujahid Danial Muzafar; Nur Anis Zahra Rosman; Nur Musfirah Abdu Aziz, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study explores medication adherence challenges in the elderly population, focusing on the complexities and dynamics of managing polypharmacy in a geriatric care setting. The research was conducted in One Stop Home Care Centre, Sri Damai, Kuantan, Malaysia, involving 10 participants aged between 45 and 72. It employs a mixed-methods approach, utilizing structured questionnaires and in-depth interviews to assess medication adherence behaviours and the influencing factors. The findings indicate a significant discrepancy between self-reported medication adherence and actual practices. While 50% of participants reported managing a single medication, observational data revealed a more intricate medication regimen, with some managing up to four different medications. The study highlights the critical role of social support systems in promoting medication adherence, with all participants adhering to their prescribed schedules due to robust caregiver involvement. However, 30% reported occasional lapses due to the complexity of their medication regimens. Notably, side effects like headaches and sleepiness were identified as key factors affecting medication adherence, underscoring the need for tailored approaches to manage side effects. The study emphasizes the importance of understanding the unique characteristics and challenges of medication adherence in the elderly, especially in the context of polypharmacy. The research also points out the socio-economic impact of an aging population and the growing demand for age-appropriate healthcare services. It emphasises the need for strategic health policy and planning to cater to the unique needs of the elderly. The findings advocate for comprehensive patient education, shared responsibility between residents and caregivers, and the implementation of systems to monitor medication intake and side effects. The study therefore provides valuable insights into medication adherence among the elderly, highlighting the necessity for personalised interventions and strategies to enhance health outcomes in this demographic. The research also acknowledges limitations, including a one-time visit for data collection and the lack of long-term follow-up, suggesting areas for future research.